DETERMINANTS OF VERTICAL COORDINATION OPTION CHOICES AMONG SMALLHOLDER FRENCH BEANS PRODUCERS IN KENYA - Naomi Chebiwot CHELANGA (Slovak University of Agriculture, 2021)
Research background: With market liberalization and the introduction of the new Global GAP measures, several vertical coordination options have emerged, presenting smallholder farmers with multiple market outlets. The choice of any vertical coordination option (VCO) is likely to be entwined by farm, farmer and vertical coordination attributes, yet the selection of an appropriate market outlet for delivering farm produce is not clear-cut. Purpose of the article: This study determines factors influencing the choice of vertical coordination options among smallholder French beans producers in Murang’a South Sub-County Methods: Using data from a sample of 215 smallholder producers, the study employed a multivariate probit model (MVP) to explain the determinants of vertical coordination option choices among French beans farmers in four wards located in Murang’a South Sub-County. Findings & Value added: The results indicate that the choice of vertical coordination option was significantly influenced by gender, household size, education stock, group membership, extension service, training access, farming experience, off-farm income, credit access, distance and market reliability. This implies that the promotion of collective action as an institutional tool for linking farmers to high-value markets, matters. These networks will aid in sharing knowledge, increasing borrowing power and thus, producers can improve French bean quality as required by the market. Additionally, financial institutions stakeholders should develop policies that favour the acquisition of credit at affordable rates. Further, the government with other relevant stakeholders should conduct more training on global gap standards.